Malaysian MOOCs: students' patterns of interaction / Nuraihan Mat Daud, Lilisuriani Abdul Latif@Bapoo and Nor Shidrah Mat Daud - Mat Daud, Nuraihan; Abdul Latif@Bapoo, Lilisuriani; Mat Daud, Nor Shidrah (UiTM Press, 2016)
Massive Open Online Courses (MOOCs) provide an interactive avenue for an unlimited number of participants to interact and collaborate on joint projects. Realizing the potential of MOOCs in accommodating more and diverse learners, four MOOCs were introduced by the Malaysian Ministry of Education in 2014. These courses allowed students from all Malaysian public higher educational institutions to benefit from the shared content. They were expected to discuss issues related to their field of studies and share their experiences. Postings sent were analyzed to study their patterns of interaction particularly the number of postings, threads and patterns of turn-taking. The contents of the messages were also analyzed to determine if they reflected effective learning. The study found that there was not much evidence of collaborative learning and co-construction of knowledge. There was a high percentage of greetings and sharing of 'words of wisdom' compared to discussions on issues related to the lessons taught. It was also observed that they wrote much more in the reflection page than in the discussion forum.